Flexible Coatings: Flexible Hard Coating: Glass‐Like Wear Resistant, Yet Plastic‐Like Compliant, Transparent Protective Coating for Foldable Displays (Adv. Mater. 19/2017). Issue 19 (May 2017) - Choi, Gwang‐Mun; Jin, Jungho; Shin, Dahye; Kim, Yun Hyeok; Ko, Ji‐Hoon; Im, Hyeon‐Gyun; Jang, Junho; Jang, Dongchan; Bae, Byeong‐Soo
Abstract : An optically transparent epoxy‐siloxane molecular hybrid material that simultaneously exhibits glass‐like wear resistance and strength, plastic‐like modulus and a high modulus of resilience is developed by Byeong‐Soo Bae and co‐workers, as described in article number1700205 . This hybrid material is utilized as a flexible hard coating on a plastic film for use in cover windows of foldable displays, which represents high pencil hardness, excellent abrasive resistance and flexibility.